Comparison of Recovery Rate of Otomycosis using One-Percent Gentian Violet and One-Percent Clotrimazole Topical Treatment - Dhakal, Srijana; Bagale, Gyanendra; Nepal, Ajit; Yadav, Deepak; Khadka, Chetan; Joshi, Deepa (Journal of Nepal Health Research Council, 2024)
Background: Otomycosis is a fungal infection of external auditory canal with worldwide prevalence of 9% to 30%. Treatment includes elimination of predisposing factor, thorough canal cleaning and topical or systemic antifungal agents. Clotrimazole is a specific topical antifungal agent with effectiveness varying from 95% to 100%. Gentian violet is an aniline dye and its use as antifungal has been mentioned in literature with effectiveness up to 80%. This study was aimed at comparing the effectiveness of these two commonly used treatments in otomycosis.This is a conducted in Department of ENT-HNS, Patan Academy of Health Sciences, Lalitpur, Nepal over one-year period after approval from institutional review committee. Patients with otomycosis were randomized into arm A and arm B group. Arm A patients were treated with one percent clotrimazole topical drops. Patients in Arm B were treated with application of one percent Gentian Violet paint. Effectiveness was measured on the basis of clinical response and recovery at end of second week. Data analysis was done with Epi Info application. Chi-square test was used and p-value less than 0.05 was considered significant. Results: Total 90 patients were treated for otomycosis over one year. Recovery was better in clotrimazole group at second week i.e., 86.84% vs 71.43%. Conclusions: Clotrimazole was more effective in treatment of otomycosis compared to Gentian Violet paint, though the result was not statistically significant. Keywords: Antifungal agent; external auditory canal; otalgia.